Tanggung Jawab Pelaku Usaha Dalam Penjualan Dengan Menggunakan Fake Order Pada Jual-Beli Online - Andrean, Paulus; Berlianty, Teng; Kuahaty, Sarah Selfina (Faculty of Law Universitas Pattimura, 2024)
ABSTRACT: Article 9 and Article 10 UUPK prohibit business actors from offering, promoting or advertising goods and services in a dishonest manner, as well as containing information that is incorrect or misleading to consumers. However, in reality there are shop owners trying to attract consumers' attention (a shortcut), by asking for help from their closest friends and family to take part in carrying out fake orders. Fake orders made by shop owners aim to increase sales. The aim of this research is to find out and explain the responsibility of business actors regarding sales by carrying out fake orders, as well as to find out and explain the forms of legal protection for consumers in buying and selling transactions through sellers who carry out fake orders. Normative juridical research method by examining library sources. The responsibility of business actors is part of the obligations that bind business activities. Article 1365 of the Civil Code as an article on unlawful acts makes several elements of (liability based on fault). The principle of responsibility based on fault (liability based on fault) is the most popular principle and is one of the principles for responsibility, so that error is the only factor in the birth of responsibility. As for preventive legal protection, efforts to prevent legal violations before they occur direct government action to be careful in making decisions based on discretion and prevention through the establishment of clear legal norms, legal education to the public, and effective law enforcement. Meanwhile, repressive legal protection, law enforcement against violations that have occurred, such as prosecution and trial. Aims to resolve the case, until it is handled by the competent judicial institution.